Early Learning 2017
DOI: 10.4324/9781315429977-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Scaffolding Experiences for the Youngest Visitors in Museums

Abstract: Research demonstrates that children have vast potential to expand their knowledge base with simple supports from adults and older children. Children's museums have a heightened awareness of the value in and the need to reach out to support adults accompanying children, thus bringing about an emphasis on family learning. Iterative exhibition studies conducted at The Children's Museum of Indianapolis illustrate the impact of planning for family learning. But for any museum, intentionally applying the strategy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 0 publications
0
19
1
4
Order By: Relevance
“…Downey et al [15] highlighted three main barriers to parent involvement: (1) most parents lack a clear understanding of the benefits of play in children's museums (2) parents lack confidence in, and knowledge of, how to play with children in a children's museum, and (3) the nature and design of children's museums may not fully encourage and facilitate parent involvement. In using child-centred approaches museum professionals tend to emphasise the importance of individual discovery and downplay the role of teaching [36]. We suggest that there should be meaningful roles for parents at most exhibits through extending and enriching children's activity through assistance and conversation.…”
Section: Understanding Factors Affecting Scaffoldingmentioning
confidence: 95%
“…Downey et al [15] highlighted three main barriers to parent involvement: (1) most parents lack a clear understanding of the benefits of play in children's museums (2) parents lack confidence in, and knowledge of, how to play with children in a children's museum, and (3) the nature and design of children's museums may not fully encourage and facilitate parent involvement. In using child-centred approaches museum professionals tend to emphasise the importance of individual discovery and downplay the role of teaching [36]. We suggest that there should be meaningful roles for parents at most exhibits through extending and enriching children's activity through assistance and conversation.…”
Section: Understanding Factors Affecting Scaffoldingmentioning
confidence: 95%
“…Most research studies documenting family visits to museums undertaken in the United States of America conclude that the main reasons for visits are to share social experiences and to learn together (Ash 2003;Dierking 1989;Haden 2010;Henderson and Atencio 2007;Melber 2007;Nadelson 2013;Puchner et al 2001;Wolf and Wood 2012). Moran, in an examination of family learning in different countries, defines family learning as 'adults and children learning together.…”
Section: Families Learning Together In Museumsmentioning
confidence: 99%
“…Ash states, 'Museums are places where families play, talk and learn from each other ' (2003: 138). Studies find that the particular mechanism which enables children's learning is the active support of their parent or caregiver in the form of questioning, explanation or guidance (Crowley and Jacobs 2002;Dooley and Welch 2013;Dunn 2012;Fender and Crowley 2007;Haas 1997;Haden 2010;Melber, 2007;Nadelson 2013;Palmquist and Crowley 2007;Puchner et al 2001;Wolf and Wood 2012). For example, Crowley and Jacobs (2002) analyzed family conversations about fossil identification in a children's museum and found that children who had received more support from parents were able to identify more fossils.…”
Section: Families Learning Together In Museumsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning, in these environments, is designed to occur through physical exploration with the exhibits with educational objectives identified and questions provided to facilitate this learning (Henderson & Atencio, 2007). In more recent years children's museums have focused on defining the early learning experiences available for children, according to areas of learning such as mathematics or science, as well as exploring how adults, especially parents, may support these experiences (Shine & Acosta, 2000;Wolf & Wood, 2012).…”
Section: Play and Learning In Young Childrenmentioning
confidence: 99%